Of Media, Social Network And Openness In Political Conversations - Ting, Su Hie; Sharifah Sophia, Wan Ahmad (2017)
Democratic citizenship is an integral part of democracy. Citizens in a democracy need to have certain types of political knowledge which guide their behaviour and influence their attitudes and values towards issues and happenings on politics. Agents for political socialisation include family, educational institutions, peers and media. The study examines the influence of media, political knowledge, efficacy and social network on openness in political conversations. In this study, the word “politics” is defined narrowly to encompass election issues. A questionnaire survey is conducted among an educated population with varying levels of political knowledge and engagement. The questionnaire, adapted from Moy and Gastil (2006), measured the respondents’ willingness or reluctance to engage in political disagreements. The antecedent variables examined are network size and heterogeneity, media use, political knowledge and efficacy. The results which reveal openness to political views with respect to election issues will provide an indication of the perceived acceptance towards democracy of political views in the Malaysian society.